2009
DOI: 10.3899/jrheum.080626
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Leptin and Adiponectin Concentrations During Tumor Necrosis Factor Blockade in Patients with Active Rheumatoid Arthritis

Abstract: In patients with RA, chronic inflammation and its suppression during anti-TNF therapy have limited influence on plasma leptin concentrations, while significantly decreasing circulating adiponectin levels. Our findings question the suggested key role of inflammatory markers in regulating adipocytokine patterns in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
3
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 36 publications
6
51
3
4
Order By: Relevance
“…Other studies have shown that anti-TNF-α therapy significantly increases serum adiponectin levels two and six weeks following therapy in RA patients (18). Contradictory to these results, another study reported that a short-or longterm TNF-α blockade alone had no affect on circulating leptin and adiponectin concentrations in RA patients, while patients treated with anti-TNF-α and concomitant corticosteroids on a regular basis demonstrated a significant decrease in adiponectin levels six months after therapy (19). Furthermore, visfatin was not associated with inflammation in patients with severe RA undergoing anti-TNF-α therapy (20).…”
Section: Discussionmentioning
confidence: 69%
“…Other studies have shown that anti-TNF-α therapy significantly increases serum adiponectin levels two and six weeks following therapy in RA patients (18). Contradictory to these results, another study reported that a short-or longterm TNF-α blockade alone had no affect on circulating leptin and adiponectin concentrations in RA patients, while patients treated with anti-TNF-α and concomitant corticosteroids on a regular basis demonstrated a significant decrease in adiponectin levels six months after therapy (19). Furthermore, visfatin was not associated with inflammation in patients with severe RA undergoing anti-TNF-α therapy (20).…”
Section: Discussionmentioning
confidence: 69%
“…The required number of participants was inferred by results of studies analyzing adipokines in painful conditions, such as rheumatoid arthritis (16) and headache (17). We concluded that 25 patients would be required in each group to detect a 20% difference in adipokines and cytokines levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest so far study including 97 patients with RA, serum adiponectin was increased after 12 months of anti-TNF treatment (Nishida, Okada et al 2008), an observation also confirmed in smaller reports with the same follow-up period, implying a potential underlying mechanism for CV risk reduction by anti-TNF agents (Komai, Morita et al 2007;Serelis, Kontogianni et al 2008;Engvall, Tengstrand et al 2010). In contrast, with the exception of the Japanese study by Komai et al who revealed increased adiponectin levels as soon as 2 and 6 weeks, no changes or reduction in adiponectin levels have been reported by studies with a follow-up period of 6 months (Derdemezis, Filippatos et al 2009;Popa, Netea et al 2009). …”
Section: Ramentioning
confidence: 35%
“…As expected, in contrast to adiponectin, which was negatively associated with CRP, leptin and resistin levels were positively linked to CRP titers (Yoshino, Kusunoki et al 2011). While anti-tumor necrosis factor alpha (anti-TNF) treatment in RA patients does not change the levels of circulating visfatin and leptin (Popa, Netea et al 2009;Gonzalez-Gay, VazquezRodriguez et al 2010), data on adiponectin is contradictory. In the largest so far study including 97 patients with RA, serum adiponectin was increased after 12 months of anti-TNF treatment (Nishida, Okada et al 2008), an observation also confirmed in smaller reports with the same follow-up period, implying a potential underlying mechanism for CV risk reduction by anti-TNF agents (Komai, Morita et al 2007;Serelis, Kontogianni et al 2008;Engvall, Tengstrand et al 2010).…”
Section: Ramentioning
confidence: 88%